Associations of Visceral Adiposity Index and Body Roundness Index with chronic kidney disease in a Hakka population: mediating effect of blood pressure - Su, Jinxia; Huang, Shengzhu; Zhao, Binran; Tan, Qiuyan; Li, Shanshan; Huang, Jing; Hu, Boning; Li, Xiaolai; Li, Bijun; Li, Chen; Mo, Zengnan; Pan, Ling; et al. (Frontiers in Nutrition, 2026)
ObjectiveThis study aims to investigate the prevalence of chronic kidney disease (CKD) and explore the associations of the Visceral Adiposity Index (VAI) and Body Roundness Index (BRI) with CKD risk in the Hakka population, while quantitatively assessing the mediating effects of blood pressure indicators.MethodsData for this study were obtained from a cross-sectional survey conducted in Bobai County, Guangxi, which included 8971 adult participants. Log-binomial regression, robust Poisson regression, and restricted cubic spline regression were used to evaluate the associations between the VAI/BRI and CKD risk. Mediation analysis was further conducted to assess the role of blood pressure parameters in these associations.ResultsThe overall prevalence of CKD was 12.62% in the study population. In the fully adjusted multivariable model (Model 3), compared with the lowest quartiles (Q1, reference), the highest quartiles (Q4) of both VAI and BRI were significantly associated with increased risks of CKD, with prevalence ratios of 1.61 (95% CI: 1.32–1.98) and 1.26 (95% CI: 1.05–1.52), respectively. Restricted cubic spline analysis revealed nonlinear associations between VAI/BRI and CKD risk, with accelerated risk increments at higher levels of both indices. Mediation analysis revealed that blood pressure indicators significantly mediated the VAI/BRI-CKD relationships, with notably stronger effects observed for BRI (SBP: 42.69%; DBP: 51.16%; MAP: 53.38%) compared to VAI (SBP: 21.4%; DBP: 28.15%; MAP: 28.41%). Additionally, PP exhibited a significant mediating effect only in the BRI-CKD pathway (12.21, 95% CI: 7.28–20.70).ConclusionThe VAI and BRI were independent risk factors for CKD in Hakka Biobank (HKB), with their associations with CKD are partially mediated by blood pressure. Given their ease of measurement and cost-effectiveness, VAI and BRI may serve as practical screening tools for identifying CKD high-risk individuals in community populations, thereby enabling early intervention and targeted prevention strategies of CKD.